Is there a risk of early relapse in patients with acute lymphoblastic leukemia presenting with bone-associated symptoms? Children with bone pain - Temuroğlu, Aytül; Güler, Salih; Aksoy, Gökalp Rüstem; Evim, Melike Sezgin; Güneş, Adalet Meral (Journal of Surgery and Medicine, 2023)
Background/Aim: Acute lymphoblastic leukemia (ALL) is the most common malignancy in childhood. Patients usually present with fatigue, pallor, weight loss, and joint and/or bone findings. However, the effects of bone-associated symptoms on prognosis remains controversial. We aimed to demonstrate whether bone-associated symptoms affect prognosis in children with ALL. Methods: This retrospective cohort study included the data from 268 patients with ALL who were diagnosed and treated between January 2011 and December 2020. The patients were divided into two groups as those with and without bone-associated symptoms. We compared the groups in terms of age, gender, immunophenotyping, day 8 prednisolone response, and risk groups, in addition to minimal residual disease (MRD), relapse, and survival rates. Results: Eighty-five out of 268 (32%) children had bone-associated symptoms at the time of diagnosis, whereas others (n=183) had none of these symptoms. The relapse rate in children with bone-associated symptoms was found to be higher than the others (17.6% versus 12%), but the difference was not significant (P=0.24). However, children with bone findings developed earlier relapse when compared with the others (18.6 versus 28.6 months; P<0.001). Conclusion: Therefore, we suggest that bone-associated symptoms at the time of diagnosis could be considered a warning sign for earlier relapse, and these children should be carefully followed.